Repurposing of Furin Inhibitors to Reduce Pathogenic E. coli- and Shigella flexneri-Induced Cytotoxicity, Oxidative Stress and Inflammation in Mammalian Epithelial Cells - Isabella Rumer; Lilla Tóth; Annelie Wohlert; András Adorján; Ákos Jerzsele; Roman W. Lange; Torsten Steinmetzer; Erzsébet Gere-Pászti (Antibiotics)
Background/Objectives: Enterobacteriaceae, including pathogenic Shigella (S.) flexneri and Escherichia (E.) coli, cause severe gastrointestinal infections through toxins like Shiga and Shiga-like toxins. Antibiotic use is often discouraged due to its potential to increase toxin effects or contribute to the development of resistance. The host protease furin is capable of activating several viral glycoproteins and bacterial toxins, thus enhancing pathogen infectivity. Methods: To assess the therapeutic potential of furin inhibitors, cultured epithelial cell models (IPEC-J2 and MDCK) were used. The effects of MI-1851 and MI-2415 were evaluated after short-term (2 h) and long-term (6 h) exposure to S. flexneri, enterohemorrhagic E. coli (EHEC), and enteropathogenic E. coli (EPEC). Cytotoxicity was determined using the CCK-8 assay, and the inflammatory response was assessed by measuring interleukin (IL)-6 and IL-8 levels. Additionally, extracellular hydrogen peroxide production was monitored in IPEC-J2 cells to evaluate the potential alterations in redox status. Results: Infections with EHEC, EPEC, and S. flexneri significantly reduced the viability of epithelial cells after 6 h of incubation. Furin inhibitors MI-1851 and MI-2415 decreased cytotoxicity and compensated for IL-6 and IL-8 overproduction in cells during infection with EHEC and S. flexneri, but not in cells exposed to EPEC. In addition, they alleviated oxidative stress, particularly during S. flexneri addition. Conclusions: The development of new antimicrobial drugs that act via alternative mechanisms and effectively manage life-threatening enterobacterial infections is of key importance. Targeting furin with inhibitors MI-1851 and MI-2415, thus blocking toxin activation, could prevent the development of antimicrobial resistance, reduce the need for antibiotics and enhance overall treatment outcomes.